Bronchoscopic resection of a tracheobronchial leiomyoma in a pregnant patient. (August 2018) - Falce, K.; Guy, E.; Hyman, D.; Hotze, T.; Lazarus, D.; Bandi, V.; Parchem, J.; Davidson, C.; Munnur, U.
Highlights: Leiomyomas of the lower respiratory tract occur most often in women aged 30–40 years. Symptoms are cough, wheezing, orthopnea, hemoptysis, or recurrent pneumonia. Bronchoscopy for diagnosis or surgical resection is generally avoided in pregnancy. Bronchoscopy of a pregnant women involves multidisciplinary coordination. Abstract: Flexible bronchoscopy, therapeutic bronchoscopy and other procedures requiring anesthesia are generally avoided in pregnancy and postponed until after delivery if possible. We report a case of a parturient with an abnormal chest radiograph and mild obstructive symptoms of unknown etiology. At bronchoscopy, a tumor associated with post-obstructive suppuration was found and excised using electrocautery snare and cryotherapy, for restoration of airway patency. Coordination between pulmonary, obstetric, anesthesia, neonatology and thoracic surgery services was essential in ensuring success and the safety of the mother and fetus.